Response of Lactobacillus plantarum WCFS1 to the Gram-Negative Pathogen-Associated Quorum Sensing Molecule N-3-Oxododecanoyl Homoserine Lactone - Spangler, Joseph R.; Dean, Scott N.; Leary, Dagmar H.; Walper, Scott A. (Frontiers in Microbiology, 2019)
The bacterial quorum sensing phenomenon has been well studied since its discovery and has traditionally been considered to include signaling pathways recognized exclusively within either Gram-positive or Gram-negative bacteria. These groups of bacteria synthesize structurally distinct signaling molecules to mediate quorum sensing, where Gram-positive bacteria traditionally utilize small autoinducing peptides (AIPs) and Gram-negatives use small molecules such as acyl-homoserine lactones (AHLs). The structural differences between the types of signaling molecules have historically implied a lack of cross-talk among Gram-positive and Gram-negative quorum sensing systems. Recent investigations, however, have demonstrated the ability for AIPs and AHLs to be produced by noncanonical organisms, implying quorum sensing systems may be more universally recognized than previously hypothesized. With that in mind, our interests were piqued by the organisms Lactobacillus plantarum, a Gram-positive commensal probiotic known to participate in AIP-mediated quorum sensing, and Pseudomonas aeruginosa, a characterized Gram-negative pathogen whose virulence is in part controlled by AHL-mediated quorum sensing. Both health-related organisms are known to inhabit the human gut in various instances, both are characterized to elicit distinct effects on host immunity, and some studies hint at the putative ability of L. plantarum to degrade AHLs produced by P. aeruginosa. We therefore wanted to determine if L. plantarum cultures would respond to the addition of N-(3-oxododecanoyl)-L-homoserine lactone (3OC12) from P. aeruginosa by analyzing changes on both the transcriptome and proteome over time. Based on the observed upregulation of various two-component systems, response regulators, and native quorum sensing related genes, the resulting data provide evidence of an AHL recognition and response by L. plantarum.